The influence of supervision Implementation by school principal, school climate, and work motivation on performance of madrasah aliyah of Palembang state teacher - Karoma Karoma (Universitas Negeri Padang, 2019)
The Influence of Supervision Implementation by School Principal, School Climate, and Work Motivation on Performance of Madrasah Aliyah of Palembang State Teacher, Dissertation of Graduate Program at State University of Padang. Population 141 teachers, research sample 60 (42.55%) teachers. Proportional sampling of random sampling based on education level, class and years of service. Data collected through questionnaires that have been tested for validity and reliability, and data analyzed by path analysis techniques. The findings indicate that Supervision Implementation by the Principal directly affects Teacher Performance 15.3%, Supervision Implementation by Principal Affects Teacher Performance through Work Motivation 8.29%, School Climate directly affects Teacher Performance 30.7%, School Climate influences on Job Performance through Work Motivation 16,64%, Work Motivation Influence on Teacher Performance 54,2%, Supervision Implementation by Principal, School Climate, and Work Motivation together influence to Teacher Performance 99,5%. Keywords: supervision, school climate, motivation, and teacher performance.